Transforming future water security - International Water Management Institute (International Water Management Institute, 2024)
Water security is essential for a safe, just and sustainable future. The IWMI Strategy 2024–2030 is an ambitious agenda for research and innovation on water security. It reflects the complexity and severity of current and future challenges in water management. It aims to use research for development to accelerate progress on Sustainable Development Goal 6 (SDG 6) – Ensure availability and sustainable management of water and sanitation for all – as well as national and regional development priorities. In 2024–2030, IWMI will apply agile, interdisciplinary and systems-oriented research for development to address complex water problems.